2019
DOI: 10.1038/s41398-019-0423-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender bias in the experimental neurosciences: the case of the maternal immune activation model

Abstract: Recent and rapidly developing movements relating to the increasing awareness and reports of gender bias, discrimination, and abuse have reached the academic environments. The consideration that negative attitudes toward women and abuse of power creates a hostile environment for female scientists, facilitating sexual harassment and driving women out of science, can be easily related to. Rationally inaccessible gender biases are not only evident at the level of the researchers, but are also paralleled by a corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 83 publications
2
45
0
Order By: Relevance
“…The above results demonstrate that minocycline treatment during the juvenile period alleviated behavior deficits in locomotor activity, sensory gating, and cognitive ability induced by prenatal poly (I:C) insult, but not social withdrawal in male offspring. Considering the possibility of the sex-specific effects in animal behaviors of MIA, the female offspring were also used in behavior tests [ 45 47 ]. We found that the female mice exposed to MIA have similar behavior deficits as male mice, and minocycline treatment can prevent these behavior deficits effectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The above results demonstrate that minocycline treatment during the juvenile period alleviated behavior deficits in locomotor activity, sensory gating, and cognitive ability induced by prenatal poly (I:C) insult, but not social withdrawal in male offspring. Considering the possibility of the sex-specific effects in animal behaviors of MIA, the female offspring were also used in behavior tests [ 45 47 ]. We found that the female mice exposed to MIA have similar behavior deficits as male mice, and minocycline treatment can prevent these behavior deficits effectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a related rat model of MIA, inflammation induced in lactating dams resulted in the development of distinct sex-dependent phenotypes in the suckling offspring, where the females offspring displayed a depressive phenotype and male offspring displayed a psychiatric phenotype (Arad et al, 2017). Taken together, the complicated and often conflicting results from these studies demonstrate the need for sex by treatment analyses in future MIA research (Coiro and Pollak, 2019; Kentner et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
“…Offspring of treated dams display behavioral and neuropathological profiles consistent with psychiatric illness in humans (Brown and Meyer, 2018). The majority of MIA studies focus on the male offspring or lack consideration of sex as a biological variable despite policies by the National Institute of Health and other grant funding agencies that require the examination of sex as a factor in biomedical research (Clayton and Collins, 2014; Coiro and Pollak, 2019). This is particularly concerning for studies of MIA given the sex differences noted in the human psychiatric disorders associated with MIA as a risk factor (Klein and Corwin, 2002; Arad et al, 2017; Brown and Meyer, 2018; Coiro and Pollak, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In general, MIA associated behavioral and neurophysiological outcomes may appear differentially, or similar behavioral phenotypes can be mediated by separate underlying mechanisms (Sorge et al, 2015), as is probable with the social discrimination impairments observed here. Notably, the paucity of female impairments reported following MIA are likely due to experimental biases, leading to the exclusion of female animals in research (Coiro & Pollak, 2019) and deficits in the detection of such impairments.…”
Section: Discussionmentioning
confidence: 99%